Peranan Tari Mancak Padang Pada Upacara Urak Balabek Di Nagari Pauh IX Kota Padang - Yolanda Afika Putri; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2021)
This study aims to describe and analyze the role of Mancak Padang dance at Urak Balabek ceremony in Nagari Pauh IX, Padang City. This research belongs to a qualitative research using a descriptive analysis method. The instrument in this study was the researcher itself and was assisted by supporting instruments such as writing tools, a camera, and a tape recorder. Types of data used were primary and secondary data. The data were collected through literature study, observation, interview, and documentation. The data analysis was done by collecting the data, describing the data, and concluding the data. The results show that Urak Balabek ceremony in Nagari Pauh IX Padang City is a ceremony held every 5 years. Urak Balabek ceremony is attended by all sasaran (martial art schools) in tapian (areas that have martial art schools) in Nagari Pauh IX. Urak Balabek ceremony is an activity to malewakan gala (title promotion of martial arts teachers) for martial art players and teachers to get a higher level of the title. The level of the teachers’ titles consists of 1. kako pandeka (first level), 2, niniak mamak (second level), 3. guru gadang (third level), 4. guru tuo (fourth level). All Urak Balabek ceremonial processions must be carried out because they are part of the appointment of martial art teachers starting from the procession to malewakan gala. The implementation of the malewakan gala (title promotion of martial arts teachers) is to achieve all levels of the existing titles. To achieve the title of guru tuo (lowest level) is from being teachers assistant (fighters who have good martial arts abilities). In the procession of malewakan gala, Mancak Padang dance must be performed by the teachers’ assistant and guru tuo. This is due to the fact that both guru tuo and guru gadang candidates must perform their abilities and skills to play the sword (mangilekan padang). After the performance of Mancak Padang dance, an oath and promise are carried out by guru tuo. Then the mimpantan (the persons who hosts Urak Balabek ceremony) first calls the title of guru tuo to the newly person appointed to have guru tuo status.The role of Mancak Padang dance at Urak Balabek ceremony plays a very important role due to the fact that it is performed and displays dexterity in playing the sword, so Mancak Padang dance is a medium which promotes the titles of martial arts teachers in the procession of mangilek an padang legalizing and validating gala or the teachers’ status to be appointed.